Comparison of the finger-feeding versus cup feeding methods in the transition from gastric to oral feeding in preterm infants, - Cláudia M.D. Moreira; Regina P.G.V. Cavalcante-Silva; Cristina I. Fujinaga; Francine Marson
Abstract Objectives: To assess the finger-feeding technique when compared with the cup feeding method during the early stage of preterm infant feeding transition regarding milk loss, milk ingestion period, and complications. Methods: Experimental, randomized, prospective study including 53 preterm infants with gestation age < 37 weeks, clinically stable, and with a score of >28 points in the Oral Feeding Readiness Assessment Scale. The preterm babies were randomized to be included in the control group, which underwent the feeding transition using a cup or in the experimental group, which used the finger-feeding technique. The analysis of data was performed using Student's t-test to evaluate differences between mean values of the appointed variables, and Fischer's test for categorical variables; the asymmetric variables were assessed by the Kruskal-Wallis ANOVA test. Results: When compared with the control group, the experimental group showed lower milk loss, longer milk ingestion time, and a lower frequency of complications during feeding. The significance level was set at 5%, with a confidence interval of 90%. Conclusion: The finger-feeding technique was shown to be a better feeding transition method regarding efficacy when compared with cup feeding method, due to lower milk loss and fewer complication episodes.